N-Methyl deuterated rhodamines for protein labelling in sensitive fluorescence microscopy. Issue 29 (7th July 2022) - Roßmann, Kilian; Akkaya, Kerem C.; Poc, Pascal; Charbonnier, Corentin; Eichhorst, Jenny; Gonschior, Hannes; Valavalkar, Abha; Wendler, Nicolas; Cordes, Thorben; Dietzek-Ivanšić, Benjamin; Jones, Ben; Lehmann, Martin; et al.
Abstract : Deuteration enhances photophysical and chemical properties of fluorescent rhodamine dyes for higher brightness in sensitive microscopy. Abstract : Rhodamine fluorophores are setting benchmarks in fluorescence microscopy. Herein, we report the deuterium (d12) congeners of tetramethyl(silicon)rhodamine, obtained by isotopic labelling of the four methyl groups, show improved photophysical parameters ( i.e. brightness, lifetimes) and reduced chemical bleaching. We explore this finding for SNAP- and Halo-tag labelling in live cells, and highlight enhanced properties in several applications, such as fluorescence activated cell sorting, fluorescence lifetime microscopy, stimulated emission depletion nanoscopy and single-molecule Förster-resonance energy transfer. We finally extend this idea to other dye families and envision deuteration as a generalizable concept to improve existing and to develop new chemical biology probes.